Perbandingan Regulasi Pengelolaan Limbah Pembangkit Listrik Tenaga Surya di Indonesia, Eropa, dan Amerika - Aslihatin Zuliana; Irwan Triadi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The development of Solar Photovoltaic Power Plants (SPPVs) as Renewable Energy in Indonesia is increasingly growing. However, SPPVs have a relatively short lifespan, necessitating the proper management of their waste, particularly solar panels. This research aims are, firstly, to analyse the regulations governing the parties responsible for managing waste from SPPVs that have reached the end of their lifespan. And, secondly, to compare waste management regulations for solar panels implemented in Europe and America as best practices for handling end-of-life SPPV waste. This research employs a normative juridical and comparative-descriptive research method, comparing regulations and implementation of SPPV waste management in Indonesia and other countries. The Finding of this research are in line with Law No. 32 of 2009 on Environmental Protection and Management and Government Regulation No. 22 of 2021, which states that any person or business entity generating waste is obligated to handle and restore it, in practice, the Power Purchase Agreement stipulates that waste management of SPPVs is the responsibility of the winning Project Company (in this case, the Consortium). And, in Europe and several US states have issued regulations for managing waste from end-of-life SPPVs. These regulations require solar panel manufacturers to have a recycling program for their own products after their end-of-life. However, managing end-of-life solar panel waste is a complex issue that requires cooperation from various stakeholders, including the government, project companies, and solar panel manufacturers. Adopting waste management policies from Europe and America is recommended to ensure that SPPV waste management is conducted responsibly and environmentally friendly.